(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the prevalence, patterns, and related factors sleep disturbances using the Sleep-50 scale in patients with Alzheimer’s disease (AD) receiving treatment at the National Institute of Mental Health. Subjects and methods: A cross-sectional descriptive study was conducted on 103 patients diagnosed with Alzheimer’s disease according to ICD-10 criteria. Sleep disturbances were evaluated using the Sleep‑50 questionnaire, covering nine sleep‑related domains. Results: Based on the Sleep 50, sleep disturbances were identified in 78.6% of participants. The most common disorders were insomnia (86,4%), sleep apnea (22,2%), and circadian rhythm disorder (18,5%). Among those with insomnia, difficulty maintaining sleep was the most frequent symptom (85,7%). Sleep disturbance was significantly associated with later-onset AD (OR=6,12; 95% CI: 2,22–16,89; p<0,001) and moderate–severe dementia (OR=4,8; 95%CI: 1,7–13,5; p<0,05). Conclusion: Sleep disorders are highly prevalent among Alzheimer’s disease patients, with insomnia being the most common. Sleep disturbance severity increases with age and cognitive decline. Early identification and management of sleep problems are essential to improve patients’ quality of life and support caregivers.